Taqwa as a community-based religious education model: Design, philosophy and potential - Meerangani, Khairul Azhar; Abdul Hamid , Mohammad Fahmi; Md Sharipp , Muhammad Taufik; Ahad, Norhana; Nor Muhammad , Mohamad Nidzar; Ahmad Zahidi, Muhammad Dzarif (Journal of Islamic, Social, Economics and Development, 2025)
The erosion of fundamental religious literacy among Muslim youth, particularly in Quranic recitation and prayer performance, presents a critical challenge for contemporary Islamic education. While formal instruction provides basic exposure, it often lacks contextual relevance and continuity beyond the classroom. In response to this gap, the TAQWA model; short for Transformasi Asas Quranic & Worship Advancement, was conceptualised as a community-based religious education framework aimed at revitalising fardu ‘ain practices among Muslim youth in Malaysia. This conceptual paper explores the philosophical foundation, structural design, and projected impact of the TAQWA module, highlighting its integration of Quranic literacy, prayer refinement, spiritual values, and community mentorship. Grounded in Islamic pedagogical principles and participatory action models, TAQWA offers a holistic approach to religious empowerment that emphasises internal transformation (taqwa), peer engagement, and social responsibility. The paper argues that the model holds significant potential to address youth moral crises, strengthen religious identity, and enhance university–community collaboration in religious education.